The Role of Financial Technology and Financial Literacy in Shaping Gen Z Students' Consumer Choices - Muhamad Helmi; Imam Heryanto; Destia Aktarina (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study addresses the critical issue of how financial literacy impacts the consumption behavior of Generation Z students. The primary objective is to examine the relationship between financial literacy, fintech usage, and consumption behavior among this demographic. The research employs a survey method utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model. The findings reveal that financial literacy significantly influences the consumption behavior of Generation Z students. Additionally, financial literacy positively affects the use of fintech; however, fintech usage does not significantly impact the consumption behavior of these students. The implications of this research highlight the importance of enhancing financial literacy among Generation Z to foster responsible consumption habits. However, the study's limitation lies in its focus on students from economic backgrounds, which may not fully represent the diverse perspectives within Generation Z. Future research should include a broader range of participants to gain a more comprehensive understanding of these dynamics.